1985
DOI: 10.1021/bi00331a004
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-19 nuclear magnetic resonance studies of lipid fatty acyl chain order and dynamics in Acholeplasma laidlawii B membranes. Gel-state disorder in the presence of methyl iso- and anteiso-branched-chain substituents

Abstract: The hydrocarbon chain orientational order parameters of membranes of Acholeplasma laidlawii B enriched with large quantities of a linear saturated, a methyl iso-branched, or a methyl anteiso-branched fatty acid plus small quantities of various isomeric monofluoropalmitic acid probes were determined via fluorine-19 nuclear magnetic resonance spectroscopy (19F NMR) over a range of temperatures spanning the gel to liquid-crystalline phase transitions (determined by differential scanning calorimetry). Membrane ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…Since the presence of a cyclopropane ring or a double bond on an acyl chain adjacent to the MPFA had little if any effect on the orientational ordering of the MFPA, it must be concluded that in the liquid-crystalline state the two fatty acyl chains experience a degree of independence sufficient to negate any influence of structural substitutents in one acyl chain upon the orientational order of the other. Previous 19F NMR results have demonstrated that the orientational order profiles of the MFPA chains in membranes of A. laidlawii B are highly similar in the liquid-crystalline state whether those membranes were enriched with straight-chain saturated fatty acids such as 15:0 (Macdonald et al, 1983(Macdonald et al, , 1985c 280, 290, 300, 310, and 320 K), or (D) 19:0 , 9 (240*, 250*, 260*, 270*, 280*, 280, 290, 300, and 310 K). The numbers in parentheses represent the temperatures at which the order profiles, from top to bottom, were acquired.…”
Section: Resultsmentioning
confidence: 99%
“…Since the presence of a cyclopropane ring or a double bond on an acyl chain adjacent to the MPFA had little if any effect on the orientational ordering of the MFPA, it must be concluded that in the liquid-crystalline state the two fatty acyl chains experience a degree of independence sufficient to negate any influence of structural substitutents in one acyl chain upon the orientational order of the other. Previous 19F NMR results have demonstrated that the orientational order profiles of the MFPA chains in membranes of A. laidlawii B are highly similar in the liquid-crystalline state whether those membranes were enriched with straight-chain saturated fatty acids such as 15:0 (Macdonald et al, 1983(Macdonald et al, , 1985c 280, 290, 300, 310, and 320 K), or (D) 19:0 , 9 (240*, 250*, 260*, 270*, 280*, 280, 290, 300, and 310 K). The numbers in parentheses represent the temperatures at which the order profiles, from top to bottom, were acquired.…”
Section: Resultsmentioning
confidence: 99%
“…All these changes modulate membrane fluidity so as to keep an adequate proportion of liquid-crystalline lipid in the membrane. Furthermore, pure diisomethyIpalmitoyl-phosphatidylethanolamine gives a stable lamellar phase up to 98°C, whereas dipalmitoyl-phosphatidylethanolamin¢ forms a hexagonal-ll phase above 43.5°C [42], yet the fluidity of the branched-chain phosphatidylethanolamine is less than that of the unsaturated phosphatidylcthanolamine [31]. Branched-chain fatty acids form less well-ordered gel phases and do not give rise to phase separations of proteins at temperatures below the 177 liquid-crystalline-to-gel phase transition temperature [42][43][44][45].…”
Section: Temperature-dependent Changes In Fatty Acid Compositionmentioning
confidence: 99%
“…Another important aspect is the maintenance of the bilayer phase. Branched-chain fatty acids form less well-ordered gel phases and do not give rise to phase separations of proteins at temperatures below the 177 liquid-crystalline-to-gel phase transition temperature [42][43][44][45]. This has functional consequences in.…”
Section: Temperature-dependent Changes In Fatty Acid Compositionmentioning
confidence: 99%
“…for instance, the thermal characteristics of sugar transport across the membrane [45]. Furthermore, pure diisomethyIpalmitoyl-phosphatidylethanolamine gives a stable lamellar phase up to 98°C, whereas dipalmitoyl-phosphatidylethanolamin¢ forms a hexagonal-ll phase above 43.5°C [42], yet the fluidity of the branched-chain phosphatidylethanolamine is less than that of the unsaturated phosphatidylcthanolamine [31]. Thus, it may be that the main reason why thermophiles commonly contain branched-chain fatty acids is to retain a functional bilayer tllat is not too fluid at high temperatures; thermophiles with rather low optin,~um growth temperatures, and also many me,:ephiles, also may have high contents of branched-chain fatty acids which are appropriate at lower temperatures because they give enough fluidity even in the gel phase to prevent the formation of separate liquid-crystalline domains into which proteins would aggregate.…”
Section: Temperature-dependent Changes In Fatty Acid Compositionmentioning
confidence: 99%